Removal of Cadmium (II), Chromium (III), and Lead (II) Heavy Metal Ions from Water by Graft Copolymerization of Acrylonitrile onto Date Palm Fiber Using H2O2/Fe++ as an Initiator - Faraj Ahmad Abuilaiwi (International Journal of Polymer Science)
The study is aimed at assessing how the date palm wood fibers (DPWF) can be used for the removal of heavy metals from water. The study involved examination of the radical polymerization and graft polymerization parameters such as reaction period, reaction time, monomer volume, amount of the catalyst, and concentration of initiator to obtain the maximum yield of graft polymerization. Fiber and copolymer were characterized using SEM and FT-IR spectroscopy to ensure the completion of polymerization. Hydroxylamine hydrochloride was used for treating the grafted copolymers for the preparation of polyamidoxime chelating resin, which was then examined for removing the heavy metal ions. Different resin dosages, contact time, and initial concentrations were used, and the batch technique experiment was utilized. The study also applied the Langmuir and Freundlich isotherm model, and Langmuir was found to be better. The absorption ability was found to be better for polyamidoxime resin for metal ions of cadmium (II), chromium (III), and lead (II).